Hubungan antara dinamika suhu tubuh dan leukosit perifer dengan skala skor FOUR penderita cedera otak risiko tinggi - Polapa, Mulyoni; Prasetyo, Eko; Oley, Maximillian Ch. (UNIVERSITAS SAM RATULANGI, 2016)
Abstract: One third of patients died in the hospital are patients with secondary brain injury associated with increased intracranial pressure as the main clinical manifestation. Body temperature, inflammatory response, and brain injury are strongly correlated each other. The responses manifest as hyperthermia, leukocytosis, and disturbances in respiratory and heart rates. Prognosis determination is very important at the time in Intensive Care Unit. FOUR score scale involves four components, as follows: eye response, motor response, brainstem reflexes, and respiration. This study was aimed to obtain the relationship between body temperature dynamic and total peripheral leucocyte with FOUR score in patients with high risk brain injury due to trauma. This was an observational analytical study with a cross sectional design. There were 38 patients that fulfilled the inclusion criteria at Prof Dr. R. D. Kandou Hospital Manado. The relationships between body temperature dynamic and total peripheral leukocyte with FOUR score were statistically analyzed with Pearson regression and correlation analysis (SPSS Version 22.0). The results showed that there was a negative correlation between body temperature dynamic and FOUR score (P = 0.03) meanwhile the correlation between total peripheral leukocyte and FOUR score was not significant (P = 0.420). Conclusion: Body temperature dynamic dan total peripheral leucocyte can be included in the protocol of the management of patients with brain injury.Keywords: brain injury, neuroinflammation, FOUR score, temperature, leucocyteAbstrak: Sepertiga dari pasien meninggal di rumah sakit ialah pasien yang mengalami cedera otak sekunder dengan peningkatan tekanan intrakranial sebagai manifestasi klinik utama. Suhu tubuh, respon inflamasi, dan cedera otak sangat erat kaitannya. Respon ini dimanifestasikan dengan hipertermia, leukositosis, serta gangguan respirasi dan denyut jantung. Penentuan prognosis pada saat perawatan di Unit Perawatan Intensif sangat berperan. Skala skor FOUR (Full outline unresponsiveness) melibatkan penilaian dari empat komponen berikut, yaitu: respon mata, respon motorik, refleks batang otak dan pernapasan. Penelitian ini bertujuan untuk mencari hubungan antara dinamika suhu tubuh dan total leukosit perifer dengan skor FOUR pada pasien cedera otak risiko tinggi karena trauma. Jenis penelitian ini observasional korelatif analitik dengan desain potong lintang. Terdapat 38 pasien cedera otak resiko tinggi yang memenuhi kriteria inklusi di RSUP Prof. Dr. R. D. Kandou Manado. Hubungan antara dinamika suhu tubuh dan total lekosit perifer dengan skor FOUR dianalisis dengan analisis regresi korelasi Pearson menggunakan SPSS Versi 22.0. Hasil penelitian mendapatkan hubungan negatif antara dinamika suhu tubuh dengan skala skor FOUR penderita cedera otak risiko tinggi (P = 0,03) sedangkan hubungan antara leukosit perifer dan skala skor FOUR secara statistik tidak bermakna (P = 0,420). Simpulan: Penilaian dinamika suhu tubuh dan leukosit perifer dapat dijadikan pedoman dalam penatalaksanaan penderita cedera otak.Kata kunci: cedera otak, neuroinflamasi, skor FOUR, suhu, lekosit